Potensi Ekstrak Etanol Biji Pinang sebagai Moluskisida Terhadap Keong Mas - Hadita Amila; Fitriani; Kartika Aprilia Putri; Yonadiah Dwitya; Mulia Safrida Sari (JURNAL BIOLOGICA SAMUDRA, 2026)
The golden snail is a major pest in rice cultivation. This pest attacks the vegetative phase of the plant, so that reducing rice production. Various efforts to control gold snail pests have been carried out such as the use of chemical-based molluscicides. However, this can lead to pest resistance and environmental pollution. Therefore, an alternative effort was made by using extracts Areca seed as a molluscicide. The purpose of this study was to determine the effect of ethanol extract of young and old betel nut as a molluscicide and to determine the concentration of ethanol extract of young and old betel nut which was effective as a molluscicide against golden snail pests. The research was carried out at the Universitas Samudra Laboratory in January-March 2021. Experimental design used RAL with 8 treatments and 5 replications. The application of ethanol extract of old betel nut and areca nut had a significant effect on mortality of golden snail pest but was not significantly different between treatments. The application of a single extract of young and old areca nut seeds at a concentration of 30% was very effective in increasing the mortality of golden snails by 100%, both for golden snails aged 14 days, 26 days, 60 days and adult (wild) snails.